Perancangan E-learning pada SMK Negeri 1 Bandung - Ditha Febriannisa; Leonardi Paris Hasugian (Universitas Multimedia Nusantara, 2017)
The quality of education will affect the quality of the nation and state. Indonesia is a country whose quality of education still low, to improve education in Indonesia needed an educational system that is responsive to changes and demands of the times. E-learning for SMK Negeri 1 Bandung is intended to facilitate students and teachers in sharing material and digital information that can be accessed anytime and anywhere. This web-based application is designed using Object Oriented Programming (OOP) with Unified Modeling Language (UML) tools. And using prototype system development method that aims to in the process of design and the end result of the application made can be used in accordance with the needs of SMK Negeri 1 Bandung. With the construction of this e-learning students and teachers can share information whenever and wherever. Index Term―E-learning, Object Oriented Programming, and Prototype.